Supernumerary extraction - clinical case repor (Research, Society and Development, 2021)
Objective: This study reports a clinical case of supernumerary tooth extraction between elements 23 and 24. Methodology: This is a clinical case report of a descriptive analytical nature (Pereira et al., 2018), carried out at the CEUNI dental clinic. Family, supervised internship discipline in Integrated Clinic II. Clinical case report: Male patient, 23 years old, arrived at the dental clinic of CEUNI Fametro, with the main complaint “extracting my supernumerary”, with orthodontic rights. During an anamnesis, he reports that the element is in the maxillary region, between the canine and the first premolar. The patient reports that he does not have any symptoms present, he reports that he does not have drug allergy and systemic changes that could contraindicate surgical intervention. During the intra- and extra-oral clinical examination, no alteration was observed, therefore, some complementary imaging tests were requested, such as: panoramic radiography, periapical and computed tomography. Final considerations: surgical planning for the extraction of this congenital anomaly was the most correct choice to avoid dental alignments, rotation of adjacent elements or cystic developments. Therefore, giving us an excellent prognosis to continue with orthodontic treatment.